THE EXISTENCE OF REGIONAL TAX REGULATIONS IN INCREASING REGIONAL ORIGINAL REVENUE IN THE GOVERNMENT OF CENTRAL JAVA PROVINCE - Andriani, Novi; Purnawan, Amin (Jurnal Hukum Khaira Ummah, 2023)
Balancing Funds from cen tral to specific regions in Central Java Province contributed from the balancing fund from the Year 2013-2016 on average by 98.36% while for the Revenue Only 90.37%. This indicates that local governments are still dependent on the central government. Local governments need to optimize the source of revenues sourced from the Local Revenue. Special Government of Central Java Province is regulated in Local Regulation number 2 Year 2011 on Central Java Province Tax and has been referring to Law Number 28 Year 2009 on Regional Tax and Retribution. This study aims to determine and analyze the extent of the existence of local tax arrangements in increasing local revenue in Central Java Province for the fiscal year 2013-2016. Data analysis method used is juridical empirical. The results of this study indicate that simultaneously there is the influence of Local Taxes on Local Revenue of 90% and fragmentary Local Tax positively substantially influential on Local Revenue have a significant effect positively on the Original Revenue.Keywords: Existence, Local Tax, Local Original Income